2021
DOI: 10.24875/bmhim.20000372
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis: current concepts

Abstract: Cystic fibrosis is an autosomal recessive genetic disease, mainly in Caucasian children and young adults. It is caused by pathogenic variants in the CFTR (cystic fibrosis transmembrane conductance regulator) gene, which results in increased viscosity and difficult mucus clearance. The main organ affected is the lung, the pancreas, sweat glands, intestine, liver, nasal mucosa, salivary glands, and reproductive tract. The clinical manifestations vary, ranging from the most frequent pulmonary symptoms of obstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 45 publications
0
6
0
7
Order By: Relevance
“… 112 Cystic fibrosis (CF) is a common, fatal, multisystem genetic disorder that presents as a chronic disease with an altered gut environment. 113 It is a disease caused by impaired epithelial anion transport owing to mutations in the gene encoding cystic fibrosis transmembrane regulator protein (CFTR), resulting in impaired fluid regulation and pH imbalance in multiple organs. 114 , 115 CFTR-dependent secretory responses can be replicated by intestinal organoids from CF patients, and it was found that increased ATP treatment of these organoids with forskolin causes CFTR-mediated chloride channel opening and induces fluid secretion from epithelial cells, resulting in swelling of intestinal organoids.…”
Section: The Application Of Organoidsmentioning
confidence: 99%
“… 112 Cystic fibrosis (CF) is a common, fatal, multisystem genetic disorder that presents as a chronic disease with an altered gut environment. 113 It is a disease caused by impaired epithelial anion transport owing to mutations in the gene encoding cystic fibrosis transmembrane regulator protein (CFTR), resulting in impaired fluid regulation and pH imbalance in multiple organs. 114 , 115 CFTR-dependent secretory responses can be replicated by intestinal organoids from CF patients, and it was found that increased ATP treatment of these organoids with forskolin causes CFTR-mediated chloride channel opening and induces fluid secretion from epithelial cells, resulting in swelling of intestinal organoids.…”
Section: The Application Of Organoidsmentioning
confidence: 99%
“…The recommended antimicrobial drugs are tobramycin, colistin, amikacin, aztreonam, and azithromycin. 22,23 Not unexpectedly, anti-inflammatory therapies comprise an unavoidable part of the therapeutic regimen for patients with CF. 24 The only antiinflammatory drug recommended for chronic use in patients with CF is high-dose ibuprofen.…”
Section: Introductionmentioning
confidence: 99%
“…As manifestações clínicas ocorrem ao nível pulmonar, digestório, reprodutor, glândulas sudoríparas entre outros, tendo em vista que esses locais possuem receptores para CFTR (LÓPEZ-VALDEZ et al, 2021). Nessa perspectiva, devido à relevância desse canal na manutenção fisiológica dos diversos sistemas, é fundamental entender a interferência do CFTR no estabelecimento da FC.…”
Section: Introductionunclassified
“…SINN, 2018;RIMESSI et al, 2021). Não há um consenso entre os estudos no que diz respeito a quantidade de classes relacionadas às mutações, assim existem relatos de quatro, seis e até sete classes de mutações distintas (RAFEEQ;MURAD, 2017;GENTZSCH;MALL, 2018;LEE et al, 2021;LÓPEZ-VALDEZ et al, 2021), na qual provocam disfunções na síntese proteica, em etapas distintas CFTR atua como um "portão", isto é, um canal iônico que permite a saída de íons Cl-e bicarbonato (HCO3-) pela superfície epitelial das células encontrada nas vias áreas, trato gastrointestinal e glândulas sudoríparas(GENTZSCH;MALL, 2018). O transporte inadequado do íon cloro exerce influência sobre os canais de sódio -aumenta o influxo -e interferem na absorção de água, o que reflete nas manifestações clínicas dos portadores de FC(FERNANDEZ et al, 2018).…”
unclassified
See 1 more Smart Citation